RHIZOSPHERE pH AND PHOSPHATASE ACTIVITY IN ORTHIC ALLOPHANIC SOIL UNDER Pinus radiata SEEDLINGS GROWN WITH BROOM AND RYEGRASS - Rivaie, Achmad A.; Tillman, Russ W. (Indonesian Journal of Forestry Research, 2009)
Under  Pinus radiata plantations  where  the tree spacing  is wider  and most soils are phosphorus  (P) deficient,  the radiata  tree response to P fertilizer is expected  to be more influenced  by  the interaction between  the applied  P fertilizer, the tree and understorey vegetation.  Therefore,  a better understanding of the soil P chemistry under radiata pine trees in association  with  other  plants  is required.  We investigated  the effect of broom  (Cytisus scoparius L.) and ryegrass  (Lolium multiflorum) grown  with  radiata  seedlings  in Orthic Allophanic Soil treated with  0, 50, and 100 μg P g-1  soil of TSP on the pH and phosphatase activity in the rhizosphere soils under glasshouse condition. The pHs of radiata rhizosphere soils either grown with broom or grass were lower than  those in the  bulk soils and the bulk and rhizosphere soils of grass and broom,  whether  they  were grown  alone or grown  with radiata at the  applications of 50 and 100 μg P g-1 soil. These results suggest that P application enhanced root induced acidification  in a P-deficient Allophanic Soil under radiata.  The soils in the rhizosphere of grass and broom, grown in association with radiata, were also acidified by  the effect of radiata  roots.  Acid  phosphatase  activity in soils under  radiata,  grass and broom  decreased with  an increased  rate of P application. At all P rates,  acid phosphatase activity was higher in the rhizosphere of radiata  grown  with  broom than in the bulk soils. The phosphatase activity in the rhizosphere soil of radiata grown with broom was also higher than that of radiata grown with grass, but it was slightly lower than that in the rhizosphere of broom grown  alone. These results suggest that broom may have also contributed to the higher  phosphatase  activity in the rhizosphere soils than  in the bulk  soils of broom  and radiata when they were grown  together